Surgical management of children and adolescents with upfront completely resected hepatocellular carcinoma. Issue 11 (3rd July 2018) - D'Souza, Amber M.; Shah, Rachana; Gupta, Anita; Towbin, Alexander J.; Alonso, Maria; Nathan, Jaimie D.; Bondoc, Alex; Tiao, Greg; Geller, James I.
Abstract: Background: Hepatocellular carcinoma (HCC) is an aggressive malignant neoplasm that is often chemoresistant. Complete surgical resection remains the mainstay of therapy. The role of liver transplantation (LT) in pediatric HCC is in evolution, as is the role of adjuvant chemotherapy for stage I disease. Methods: A retrospective review of patients < 18 years of age with completely resected HCC treated with surgical intervention alone at our institution from 2004 to 2015 was conducted. Results: Twelve patients with a median age of 12 years (range = 1–17; number of females = 7) with upfront resected HCC (Evans stage I) were identified. Four patients had HCC without identifiable risk factors (fibrolamellar‐HCC = 2; early HCC arising in focal nodular hyperplasia = 1, well‐differentiated [wd] HCC = 1). Four patients had early or wd‐HCC in the context of portosystemic shunts (Abernethy = 2; mesocaval shunt and portal vein thrombosis = 2). Four patients had moderate to wd‐HCC in the context of pre‐existing liver disease with cirrhosis (progressive familial intrahepatic cholestasis type‐2 = 2, alpha‐1 antitrypsin deficiency = 1, Alagille syndrome = 1). Seven patients underwent LT (multifocal = 5; solitary = 2); five exceeded Milan criteria (MC) by imaging. Five patients underwent complete resection (segmentectomy = 2; hemihepatectomy = 3). Ten patients received no adjuvant chemotherapy. All patients are alive without evidence of disease with a median follow‐up of 54.1 months (range = 28.1–157.7 months). Conclusions: Pediatric and adolescent patients with upfront, completely resected HCC can be effectively treated without chemotherapy. LT should be considered for nonmetastatic HCC, especially in the context of pre‐existing chronic liver disease, even when the tumor exceeds MC. Distinct pediatric selection criteria are needed to identify patients most suitable for LT.